The ARROWS project: adapting and developing robotics technologies for underwater archaeology. Issue 2 (2015) - Allotta, Benedetto; Costanzi, Riccardo; Ridolfi, Alessandro; Colombo, Carlo; Bellavia, Fabio; Fanfani, Marco; Pazzaglia, Fabio; Salvetti, Ovidio; Moroni, Davide; Pascali, Maria Antonietta; Reggiannini, Marco; Kruusmaa, Maarja; et al.
Abstract: ARchaeological RObot systems for the World's Seas (ARROWS) EU Project proposes to adapt and develop low-cost Autonomous Underwater Vehicle (AUV) technologies to significantly reduce the cost of archaeological operations, covering the full extent of archaeological campaign. ARROWS methodology is to identify the archaeologists requirements in all phases of the campaign and to propose related technological solutions. Starting from the necessities identified by archaeological project partners in collaboration with the Archaeology Advisory Group, a board composed of European archaeologists from outside WS, the aim is the development of a heterogeneous team of cooperating AUVs capable of comply with a complete archaeological autonomous mission. Three new different AUVs have been designed in the framework of the project according to the archaeologists' indications: MARTA, characterized by a strong hardware modularity for ease of payload and propulsion systems configuration change; U-CAT, a turtle inspired bio-mimetic robot devoted to shipwreck penetration and A_Size AUV, a vehicle of small dimensions and weight easily deployable even by a single person. These three vehicles will cooperate within the project with AUVs already owned by ARROWS partners exploiting a distributed high-level control software based on the World Model Service (WMS), a storage system for the environment knowledge, updated in real-time through online payload data process, in the form of an ontology. The project includes also the development of a cleaning tool for well-known artifacts maintenance operations. The paper presents the current stage of the project that will lead to overall system final demonstrations, during Summer 2015, in two different scenarios, Sicily (Italy) and Baltic Sea (Estonia).